수확시기와 조제방법이 청보리 사일리지의 사료가치 및 발효품질에 미치는 영향 - 송태화; Tae-hwa Song; 박태일; Tae-il Park; 한옥규; Ouk-kyu Han; 박형호; Hyong-ho Park; 조상균; Sang-kyun Cho; 오영진; Young-jin Oh; et al. (Korean journal of crop science, 2013)
This experiment was conducted to obtain basic a information on feed value and fermentative quality of whole crop barley with different harvesting time and making method. As a result, in case of feed value, crude protein, NDF and ADF content were decreased with late harvest, but TDN was increased. In the silage, the results were similar and these patterns showed the same before and after the silage making. Thus, there was no significantly difference in bale and chopper. In case of fermentative quality, pH of the silages showed increasing with late harvesting time but the contents of organic acid did lower, and those tendencies were the same in both bale and chopper condition. But the lactic acid content were approximately 23 percent higher in chopped condition. In conclusion, ensiling at yellow ripe stage is better than other stages, chopped ensiling could improve fermentation quality.